Implications of Cheap Oil for Emerging Markets - Kabundi, Alain; Ohnsorge, Franziska (World Bank, Washington, DC, 2020)
The COVID-19-triggered collapse in oil prices in March and April 2020 was the seventh, and by far the most severe, in a series of such collapses since 1970. This paper, first, compares this most recent collapse and its drivers with previous ones in an event study. It finds that it was associated with an exceptionally severe plunge in oil demand. Second, in a local projections model, this paper estimates the implications of demand- and supply-driven oil price collapses for growth in emerging markets and developing economies (EMDEs). The paper finds that steep oil price collapses were associated with significant and lasting output losses in energy-exporting EMDEs but no meaningful output gains in energy-importing EMDEs. These results are robust to multiple robustness checks.